Navigating Presales with Dual Payment Systems and Return Policies: Insights into Consumer Time Inconsistency and Corporate Strategies - Adrian Otniel Tampilang; Ngadi Permana (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review examines the effectiveness of dual payment structures and return policies in managing presales while addressing consumer time inconsistency. Drawing from diverse studies, it highlights the strategic role of these mechanisms in mitigating the effects of procrastination and post-purchase regret on consumer behavior. By synthesizing findings from behavioral economics, marketing, and operations management, the review reveals how firms can optimize revenue and enhance customer satisfaction through innovative presales strategies. Key insights include the importance of flexible return policies in building consumer trust and the integration of dual payment models to balance firm profitability and customer retention. The study also identifies limitations, such as the contextual variance of findings across industries and cultural settings, emphasizing the need for further empirical validation